A rare cause of gastric outlet obstruction - Murali, Abhishek; Krishnappa, Rohit; Murugesh, Rajesh B.; Rajagopalan, S. (International Surgery Journal, 2020)
Gastric outlet obstruction is the clinical and pathophysiological consequence of any disease process that produces mechanical impediment to gastric emptying. It may be acute from inflammatory swelling and peristaltic dysfunction or chronic from cicatrix. Chronic inflammation of the duodenum may lead to recurrent episodes of healing followed by repair and scarring ultimately leading to fibrosis and stenosis of the duodenal lumen. We would like to present a unique case of an elderly lady presenting with intractable vomiting over 3 months, gradually progressive which aggravated on consuming solids initially to consuming liquids later. After thorough investigations a provisional diagnosis of chronic duodenal ulcer with gastric outlet obstruction probably due to cicatrix was made. On laparotomy there was a chronic scarred duodenal ulcer following a previously contained perforation which was causing the gastric outlet obstruction. Cholecystectomy, duodenoplasty and loop gastrojejunostomy was performed with no complications post-operatively. This is a rare case of previous contained duodenal perforation causing gastric outlet obstruction.